Burden of pneumococcal disease in children in Cuba before the introduction of a novel pneumococcal conjugate vaccine. (2019) - Linares-Pérez, Nivaldo; Wahl, Brian; Rodriguez, Misladys; GildaToraño, GildaToraño; Toledo-Romaní, María E.
No abstract available